Hospital variation in maternal complications following caesarean delivery in the United States: 2006–2012. (22nd July 2015) - Moroz, LA; Wright, JD; Ananth, CV; Friedman, AM
Abstract : Objective: To assess hospital variability in and patient and hospital factors associated with caesarean delivery (CD) complications. Study Design: Population‐based cohort. Setting: United States delivery admissions. Population: Women who underwent a CD between 2006 and 2012. Methods: Hospital‐specific random‐effects log‐linear regression models were developed to account for patient, obstetric, and hospital risk factors related to a composite complication outcome including infection, haemorrhage, surgical complications and prolonged hospital stay. Between‐hospital variability in rates of CD complications was also estimated. Main outcome measure: Composite complication rate. Results: Among 1 339 397 women who underwent CD in 457 hospitals, 6.4% ( n = 85 838) experienced a complication. The most frequent complications were haemorrhage, transfusion, length of stay >7 days, and endometritis. Complications were strongly associated with the presence of obstetric factors and pre‐existing medical conditions. Complication rates were 54% higher among black (8.8%) than white (5.7%) women ( P < 0.001), and were more common in teaching (8.1%) than non‐teaching (5.4%) hospitals ( P < 0.001). In an adjusted model, the mean complication rate was 6.7%. A small proportion of hospitals (4.8%) had a complication rate greater than twice the mean (≥13.4%). Complications were strongly associated with the presence of obstetrical factors and pre‐existing medical conditions. Conclusions: CD complication rates are strongly associated with patient and obstetric factors. While CD complication rates may be a quality metric of limited utility given the low rate of complications across most hospitals, a small number of hospitals demonstrate particularly high rates of complications. Review of CD complication rates may be an important aspect of quality assurance processes for these centres. Tweetable abstract: A small number of hospitals demonstrate particularly high rates of caesarean complications. Tweetable abstract: A small number of hospitals demonstrate particularly high rates of caesarean complications.